Proceedings of the International Scientific-Practical Conference “Business Cooperation as a Resource of Sustainable Economic De 2019
DOI: 10.2991/ispcbc-19.2019.103
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation of the rate of Russian Arctic regions’ economic development and the innovative activities of industrial production

Abstract: Arctic regions are the most important raw material base for the further development of the Russian economy but industrial production located there operates in adverse climatic conditions and the nature is extremely vulnerable to production waste pollution. In this regard it is very important to consider the current state and prospects of innovative activities of the industry. The paper considers the method of identifying the interrelation between the rates of economic growth of production in the regions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…As follows from our earlier results [13][14][15][16], the level and growth rate of technological development should have a significant impact on the level of sustainability, which is reflected by the dynamics of the coefficient values of the level of technological production (Kutp) as the ratio of material output to stock output. Table 5 shows our calculated data on the absolute values of this coefficient and its growth rates for 2011-2020 for all twelve above-mentioned enterprises.…”
Section: Rsc Energiamentioning
confidence: 88%
See 1 more Smart Citation
“…As follows from our earlier results [13][14][15][16], the level and growth rate of technological development should have a significant impact on the level of sustainability, which is reflected by the dynamics of the coefficient values of the level of technological production (Kutp) as the ratio of material output to stock output. Table 5 shows our calculated data on the absolute values of this coefficient and its growth rates for 2011-2020 for all twelve above-mentioned enterprises.…”
Section: Rsc Energiamentioning
confidence: 88%
“…Earlier we have developed a methodology of economic analysis of technological renewal of enterprise production systems [15,16]. It is based on the calculations of three main indicators: stock return, material yield and coefficientf of the level of manufacturability of production.…”
Section: Methodsmentioning
confidence: 99%
“…In our work [12], based on the analysis of the dynamics of key performance indicators of several large industrial enterprises in Russia for a five-year period, we hypothesised that there is a proportional relationship between the values of capital output ratio (COR) of production and material output ratio (MOR) of output, which is quantitatively reflected by the proportionality coefficient. In the future, based on the study of many activities of other industrial enterprises according to the data of annual financial (accounting) statements presented on their websites, as well as consideration of the types of industrial activities of the economy of the regions -subjects of the Federation according to Rosstat, with the corresponding analysis of the dynamics of the values of COR and MOR for a long period of time (10-15 years), we have shown that, firstly, such a dependence really exists [13], and regardless of how COR is calculated: by the entire volume of fixed assets or by the total volume of fixed assets. Secondly, the specific annual values of the proportionality coefficient may vary in one direction or another, but the prevailing trend for almost all the studied objects is an increase in the values of this coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…Знак плюс (+) соответствует видам промышленной деятельности, в которых износ основных фондов в 2015 г. превысил среднероссийский уровень. Таким образом, очевидно, что в целом тенденции развития промышленности в регионах Арктики не вполне соответствуют инновационноинтенсивному направлению обеспечения экономического роста [21][22][23][24][25][26]. Наиболее сложное положение сложилось в добывающей промышленности, где в двух регионах из четырех сформировалось самое неблагоприятное неинновационое и неэффективное направление развития.…”
Section: теоретико-методологические основы управления технологическим обновлением производственных системunclassified